Pemikiran Politik Hukum Islam Muhammadiyah - Khoiri, Nispul (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2013)
The role of Muhammadiyah in Indonesias political dynamics and gait providing a large role in this country. Although the union Muhammadiyah is in neutral position not practical politics, but Muhammadiyah able to motivate, to suppport, to preseur even within the framework of political thought enforcing doing good and avoiding evil. Muhammadiyah has fixed attention on the political process of Islamic law, such as the legislative process in Parliament and took the government policy. Legislation (legislation) is part of the governments job, with the goal of creating peace, goodness and justice. When the Act was legislated derived from Islamic law, is certainly binding legal force by the Islamic Law. Yet the political role of Muhammadiyah in some cases carried out by the elite have a positive effect on political thought Muhammadiyah itself, including in this case the politics of Islamic law. Muhammadiyah is able to oversee the legislative process in Parliament. Muhammadiyah participate motivate some legislation that transforms Islamic law into national law. Such as: Act No. 14/1970 concerning Judicial Authority, Law No. 1/1974 on Marriage, Law 7/1989 On Religious Courts, Compilation of Islamic Law, Promoting Growth and Development of Islamic Banking in Indonesia, and others. Muhammadiyah also participate in creating good governance such as corruption and corrupt practices through both structural and cultural approaches. Muhammadiyah movement came to the fore as a leader in enforcing doing good and avoiding evil.